Delayed extinction fails to reduce skin conductance reactivity to fear‐conditioned stimuli. (17th June 2016) - Fricchione, Jon; Greenberg, Mark S.; Spring, Justin; Wood, Nellie; Mueller‐Pfeiffer, Christoph; Milad, Mohammed R.; Pitman, Roger K.; Orr, Scott P.
Abstract: A brief 10‐min time delay between an initial and subsequent exposure to extinction trials has been found to impair memory reconsolidation in fear‐conditioned rodents and humans, providing a potential means to reduce fearfulness in anxiety disorders and posttraumatic stress disorder (PTSD). The present study used videos of biologically prepared, conditioned stimuli (tarantulas) to test the efficacy of delayed extinction in blocking reconsolidation of conditioned fear in healthy young adults. Strong differential conditioning, measured by skin conductance, was observed among a screened subset of participants during acquisition. However, the delayed‐extinction intervention failed to reduce reactivity to the conditioned stimulus paired with the extinction delay. These results are partially consistent with other recent, mixed findings and point to a need for testing other candidate interventions designed to interfere with the reconsolidation process.